Analysis of model fit and item parameter of work and energy test using item response theory - Yustiandi Yustiandi; Duden Saepuzaman (Universitas Sultan Ageng Tirtayasa, 2021)
One of the important parts in assessing learning outcomes is using a good instrument that is analyzed using an appropriate analytical model and can measure students' abilities accurately. This study aims to determine the model fit and item parameter of work and energy test using item response theory. This research is a quantitative research that was carried out on the responses of 1177 high school students spread across Banten Province. The instrument is a set of work and energy tests consisting of 25 multiple choices. The data analysis used the item response theory approach with statistical methods ranging from determining the fit model to the item characteristics.. The analysis showed the students' responses to the fit energy and effort test with 9 items of 1 PL model, 17 items of 2 PL model, and 16 items of 3 PL model. Based on the percentage, the 2PL model is suitable than 1PL and 3PL. Further analysis determines the item parameter value by referring to the 2PL model, namely the item parameter difficulty level (b) and discrimination (a). The result shows that all items have difficulty in the range of 2.501 to 1.595, and the discrimination was in the range of 0.289 to 1.109. Based on this analysis, it can be concluded that all items in this test are the good item criteria